Determinants for the formation of socio-economic component of national security - Sievidova, I. O.; Сєвідова, І. О.; ORCID: http://orcid.org/0000-0003-3703-4610; Tkachenko, S. O.; Ткаченко, С. О.; ORCID: http://orcid.org/0000-0002-5816-4185 (Norwegian Journal of development of the International Science. - 2022. - № 85 - P. 20-22, 2022)
Розглянуто детермінанти формування соціально-економічної безпеки як невід’ємної складової національної безпеки. Проаналізовано безпеку держави. Нового значення набуває сфера аналітичного забезпечення управління економічною безпекою, особливо з посиленням цифровізації економіки та посиленням негативних наслідків глобальних економічних криз, ризиків бізнес-середовища. Розглянуто системний підхід до оцінки соціально-економічної безпеки та визначено, що соціально-економічна безпека – це стан, який характеризує захист соціально-економічної системи від загроз макросередовища. Визначено, що разом із розробленням заходів щодо зміцнення економічної безпеки як складової національної безпеки на макрорівні, значну роль відіграє управління економічною безпекою на рівні суб'єктів господарювання.

The article the determinants of the formation of socio-economic security as an integral part of the national security of the state analyzed. The field of analytical support of economic security management acquires new features with the strengthening of the digitalization of the economy and the strengthening of the negative consequences of global economic crises, risks of business environment. The definite sources of socio-economic security as an integral part of the national security of the state are analyzed. A systematic approach to assessing socioeconomic security is considered and it is determined that socio-economic security is a state characterized by the protection of the socio-economic system from macro-environment threats, which provides opportunities for selfdevelopment, conservation, an appropriate social state and level of life support in conditions of an appropriate level. profitability and consistency and the realization of economic interests. It was determined that along with the development of measures to strengthen economic security as a component of national security at the macro level, economic security management at the level of economic entities plays a significant role.

Рассмотрены детерминанты формирования социально-экономической безопасности как неотъемлемой составляющей национальной безопасности. Проанализирована безопасность государства. Новое значение приобретает сфера аналитического обеспечения управления экономической безопасностью, особенно с усилением цифровизации экономики и усилением негативных последствий глобальных экономических кризисов, рисков бизнес-среды. Рассмотрен системный подход к оценке социально-экономической безопасности и определено, что социально-экономическая безопасность – это состояние, характеризующее защиту социально-экономической системы от угроз макросреды. Определено, что вместе с разработкой мер по укреплению экономической безопасности как составляющей национальной безопасности на макроуровне, значительную роль играет управление экономической безопасностью на уровне хозяйствующих субъектов.
Sievidova, I. Determinants for the formation of socio-economic component of national security / Sievidova I., Tkachenko S. // Norwegian Journal of development of the International Science. - 2022. - № 85 - P. 20-22.- DOI: https://doi.org/10.5281/zenodo.6594364.
Keywords: Економіка. Економічні науки. Економічна безпека. Economics. Economic Security. Экономика. Экономические науки. Экономическая безопасность; Наукові публікації. Scientific publications. Научные публикации; соціально-економічна безпека; socio-economic security; социально-экономическая безопасность; структура економіки; economic structure; экономическая структура; соціальний розвиток; social development; социальное развитие; суб’єкти господарювання; business entities; субъекты хозяйствования; аналіз; analysis; анализ; контроль; control; Україна. Ukraine. Украина; національна безпека; national security; национальная безопасность